Highly-efficient flame-retarding unsaturated polyester resin via the designation of an expansive flame retardant - Ying-Ming Li; Shuang-Lin Hu; Hang-Ping Fang; Yao Deng; Chang-De Yang (Advanced Industrial and Engineering Polymer Research)
Unsaturated polyester resins (UPR) are commonly used in electronics manufacturing and traditional construction, but their inherent flammability greatly limits their use. An expansive flame retardant EZ was prepared via the simple ionic reaction between the 2-Aminothiazole (AMZ) and ethylene diamine tetra methylene phosphoric acid (EDTMP). The thermal decomposition process of EZ and UPR/EZ and the flame retardancy of the compound were studied. The flame retardancy mechanism of EZ in UPR was analyzed in detail. When the EZ content was 15 wt%, the flame-retardant grade of the composite reached V-0. The flame-retardant efficiency was very high mainly through the interaction of gas phase and condensed phase. Interestingly, flame retardant EZ can perform expansion crosslinking in UPR, which can effectively promote carbon formation in UPR. Moreover, EZ itself can also expand to form dense and continuous carbon layers in UPR, which further elucidates the flame-retardant mechanism.